FIRST SEXUAL MATURATION AND BREEDING CYCLE oF pangasius Hypophthalmus (SILURIFORMES, PANGASIDAE) REARED IN POND - Anang Hari Kristanto; Jacques Slembrouck; Marc Legendre (Research Center for Fisheries, 2005)
The age and weight at first sexual maturation and the seasonal variatrons of sexual maturity of pangasius hypohthalmus were determined on a fish group spawned in April 1997 and followed up until 32 months of age at the sukamandi RIFF station, west Java Indonesia.